PENGEMBANGAN LKPD BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP - Wenni Herviani; Agung Hartoyo; Bistari Bistari (Universitas Tanjungpura, 2020)
AbstractThis study aims to develop a worksheet (LKPD) based on the Discovery Learning to improve the mathematical creative thinking skill of Junior high school students. The method used was Research and Development (R&D). The subjects in this study were ten 8th grade students of SMP Negeri 2 Ketapang in the year 2019/2020. Data collection techniques used were interview and observation. The instruments used were LKPD validation sheets and questionnaires. Based on the result, LKPD is valid to be used on Statistics material for 8th-grade students. The large group test revealed that using the LKPD could give a positive effect to improve the mathematical creative thinking skill of junior high school students, especially on 8th-grade students of SMP Negeri 2 Ketapang. It proved by the average scores of mathematical creative thinking skill components, which were fluency = 65 categorized as